Оцінка показників якості нових рибних пресервів у вишневому соусі «Нептун Cherry» - Дітріх, Ірина Вікторівна; Марченко, Юлія Ігорівна (My University, 2015)
Розглянуто можливість отримання нових рибних пресервів у вишневом у соусі «Нептун Cherry», які мають підвищену біологічну цінність та оригінальні споживні властивості. Установлена оптимальна концентрація сухих речовин у вишневом у соку з метою надання пресервам гармонійних органолептичних властивостей. Виготовлено зразки нового продукту, визначено їх органолептичні та фізико-хімічні показники якості. The possibility of getting new fish preserves in cherry sauce «Neptune Cherry», which has high biological value and unique consumer properties: color and taste, by the addition of plant material such as fruit juice cherries. Plant ingredient, which is the main component of the sauce, was elected by geographicaccessibility, consumer properties and chemical composition for reference data. The optimum concentration of solids in cherry juice for provision of harmonic organoleptic properties to preserve is determined. Results of the assessment show that fish preserves in cherry sauce containing 11% solids in cherry juice possess the best organoleptic quality. Samples of the new product carried out through the evaluation of organoleptic characteristics of new fish preserves in cherry sauce «Neptune Cherry» is developed by the five-point scale. Physical and chemical characteristics qualities are specified.
Keywords: рибні пресерви; fish preserves; вишневий соус; cherry sauce; оселедець тихоокеанський зниженої товарної цінності; pacific herring of reduced commodity values; фізико-хімічні показники; physical and chemical quality characteristics; кафедра технології ресторанної і аюрведичної продукції